"We are All Fellow Human Beings": Mental Health Workers' Perspectives of Being in Relationships with Clients in Community-Based Mental Health Services. (1st December 2013) - Eriksen, Kristin Ådnøy; Arman, Maria; Davidson, Larry; Sundfør, Bengt; Karlsson, Bengt
<x xml:space="preserve">Abstract</x> Stable, trusting relationships are at the core of Norwegian community-based mental health services. Being acknowledged and respected may promote a client's recovery. The aim of this study was to explore mental health workers' experiences of relating to clients. The design involved multi-stage focus groups based on a participatory approach and using interpretative phenomenological analysis. Acknowledging the personhood of a client appears to offer opportunities for growth and development in the client as well as in the health worker, based on reciprocal processes of each person affecting the other and the health workers' openness to understanding the other person.